Broadband Right-Handed Circular Polarized (RHCP) Antenna with Loop Metasurfaces - A. Bakar, H.; Abd. Aziz, M. Z. A.; Ahmad, B. H.; Ghani, S.; Nornikman, H. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
In this paper, an analysis of different designs of metasurface (MS) structure of the circular polarized antenna was proposed to analyse its effects towards the antenna performance. Firstly, the antenna was designed based on an inverted suspended rectangular slot at the rectangular patch and air gap between the substrate and copper layer with a distance of 10 mm. Then, as a way to create the circular polarization, the designed antenna is added with an optimized dual circular notch at the rectangular slot. This circular polarized antenna design is a right-handed circular polarization (RHCP) with optimized rectangular slot and dual circular notch at the patch. Then, the RHCP antenna is combined with the MS design which is integrated at the copper ground layer of the antenna. The L-probe technique is used in this antenna design and the signal into the antenna structure is fed by the 50Ω probe feed SMA connector. Computer Simulation Technology (CST) Microwave Studio Suite software is used as the simulation tool for the designed proposed antenna. The result of performance in terms of return loss, bandwidth, gain, directivity, axial ratio and total efficiency for the proposed antenna at the design frequency are analysed. Comparison results of simulation show that the proposed RHCP antenna with and without MS can achieve an axial ratio below 3 dB with return loss less than -10 dB at the targeted frequency. The target application for this antenna design is the Wireless Local Area Network (WLAN) which operates at 2.4 GHz frequency.